Teacher Well-Being: the Teachers Perspective in the Special Region of Yogyakarta - Hidayati, Dian; Sukmayadi, Trisna; Luthfi Imama, Mohammad; Fadlan Syakir, Muhammad (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The role of a teacher is vital to creating an effective and efficient educational process. Not everyone can become a teacher or lecturer because they are considered a profession that demands professionalism. Nonetheless, the role of a teacher in the educational process is not commensurate with the welfare conditions felt by the teachers; the workload is quite heavy, with emotional demands causing negative suggestions for teachers regarding their work. It is appropriate for policymakers related to the world of education to pay more attention to the construct of well-being in teachers. The aim of this research, thus, is to discover teachers' perspectives on teacher well-being that they experience while being teachers, starting from two attitudes in implementing teacher well-being (affective and cognitive), as well as what factors make them persist as teachers. This research used qualitative methods. The informants involved in this research were five teachers in the Special Region of Yogyakarta. Based on the data collection method, a triangulation test of sources, techniques, and time was carried out to test the validity of the data. This research revealed six aspects of teacher well-being, encompassing positive relationships with other people, autonomy, personal growth, environmental mastery, self-acceptance, and purpose in life. Family support and a positive view of the teaching profession are essential to improving teachers' well-being.